The phenylalanine loading test in the differential diagnosis of dystonia - Bandmann, Oliver; Goertz, M.; Zschocke, Johannes; Deuschl, Günther; Jost, W.; Hefter, H.; Müller, U.; Zöfel, P.; Hoffmann, Georg F.; Oertel, W. (Neurology, 2003)
Early diagnosis of dopa-responsive dystonia (DRD) and its delineation from other dystonic syndromes is of great relevance because DRD is an eminently treatable condition. The possible relevance of the phenylalanine loading test (Phe-L) in differentiating DRD from primary focal and generalized dystonia was investigated. A marked difference in the phenylalanine/tyrosine ratio between patients with DRD and patients with other types of dystonia was observed. This indicates that Phe-L may be helpful in the differential diagnosis of dystonias.
Gesehen am 22.12.2020